Phenological responses of prairie plants vary among species and year in a three‐year experimental warming study. Issue 10 (29th October 2015) - Whittington, Heather R.; Tilman, David; Wragg, Peter D.; Powers, Jennifer S.
Abstract : As temperature is a common regulator of temperate plant phenology, future increases in global temperatures are likely to cause shifts in the timing of plant phenophases such as flowering and senescence, with potential feedbacks on species interactions and carbon cycling. We used a 3‐year field warming study in a temperate grassland to investigate the effects of two levels of warming (+ ~1.5°C and + ~3°C) on the phenology of budding, flowering onset, and peak flowering of ten perennial plant species at both individual and population scales. We also examined the effect of warming on green‐up and senescence by measuring normalized difference vegetation index (NDVI) for one year. Populations and individuals of Amorpha canescens, Dalea purpurea ( Petalostemum purpureum ), and Andropogon gerardii flowered five to eight days earlier under high warming. For seven species, interannual variability in flowering time equaled or exceeded experimental warming treatment effects in any given year. Responses to warming were not consistent among years for several species, especially Liatris aspera . Warming led to higher NDVI values in the spring, indicating that warming accelerated spring biomass growth but did not significantly affect senescence. These results suggest that the community flowering profile may be altered under warming, potentially affecting pollinator, trophic and competitive interactions, and indicate that the timing to peak biomass may be accelerated, possibly affecting ecosystem carbon cycling.